2020
DOI: 10.7759/cureus.11064
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children, the Real Disease of COVID-19 in Pediatrics - A Multicenter Case Series From Al-Ahsa, Saudi Arabia

Abstract: Fortunately, coronavirus disease 2019 (COVID-19) infection in pediatric populations exhibits a mild course of disease. However, a small number have recently been identified who develop a significant systemic inflammatory response, a new disease entity called multisystem inflammatory syndrome in children (MIS-C), especially after the peak of the wave in Al-Ahsa, Saudi Arabia, in early June to mid-July. In MIS-C children usually present a few days to a few weeks after recovery from COVID-19 with high grade fever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…Compared with multisystemic inflammatory shock in children with COVID 19 infection, the patients were significantly more hemodynamically unstable and had a higher incidence rate. Cardiovascular collapse was the cardinal sign in both KDSS and MIS-C. Globally, myocardial and valvular dysfunction are observed, but compared to what was observed here and in Almoosa et al peripheral vascular dysfunction is the main feature with minimal myocardial impairment [1,6,7].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Compared with multisystemic inflammatory shock in children with COVID 19 infection, the patients were significantly more hemodynamically unstable and had a higher incidence rate. Cardiovascular collapse was the cardinal sign in both KDSS and MIS-C. Globally, myocardial and valvular dysfunction are observed, but compared to what was observed here and in Almoosa et al peripheral vascular dysfunction is the main feature with minimal myocardial impairment [1,6,7].…”
Section: Discussionsupporting
confidence: 57%
“…One of them suggested that an unidentified infection could trigger the immune response that causes KD in genetically suspected individuals [ 1 , 2 ]. This was observed here in the study, and especially in the era of COVID 19 infection, where accurate co-recording and documentation of a previous or current COVID-19 infection increases the association between infections and the triggering of Kawasaki disease or multisystemic inflammatory shock in children with COVID-19 infection (MIS-C) [ 1 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 72%
“…There has been a striking paucity of MIS-C cases from East Asia, despite the high incidence of KD in this geographic area ( Kim et al, 2020b ; Li et al, 2019 ). Only two cases of MIS-C have been reported to date in South Korea, and no cases have been reported in Japan or China ( Toyo Keizai Online COVID-19 Task Team, 2021 ), contrasting with the higher numbers of cases from the Americas, Europe, Africa, South Asia, and the Middle East ( Almoosa et al, 2020 ; Dufort et al, 2020 ; Falah et al, 2020 ; Feldstein et al, 2020 ; Jain et al, 2020 ; Kim et al, 2020a ; Kim et al, 2020b ; Lee et al, 2021 ; Mamishi et al, 2020 ; Ulloa-Gutierrez et al, 2020 ; Verdoni et al, 2020 ; Webb et al, 2020 ). Whether this is merely due to a lower number of COVID-19 cases in East Asia remains to be seen, bearing in mind the possibility of ascertainment bias ( Fig.…”
Section: Epidemiology Of Mis-c and Kdmentioning
confidence: 99%
“…[4] The true incidence of MIS-C is still uncertain but an estimated incidence of 0.6% among laboratory con rmed COVID-19 patients has been reported in New York. [5] To date, the majority of MIS-C cases have been reported from North America and European countries with very few reports from Asian countries [4][5][6][7][8][9]. Large case series conducted in the USA and UK show that risks associated with developing MIS-C may vary by gender, age and ethnicity.…”
Section: Introductionmentioning
confidence: 99%